Effects of Particle Size, Electronic Connectivity, and Incoherent Nanoscale Domains on the Sequence of Lithiation in LiFePO4 Porous Electrodes. (1st October 2015) - Li, Yiyang; Meyer, Sophie; Lim, Jongwoo; Lee, Sang Chul; Gent, William E.; Marchesini, Stefano; Krishnan, Harinarayan; Tyliszczak, Tolek; Shapiro, David; Kilcoyne, Arthur L. David; Chueh, William C.
Abstract : High‐resolution X‐ray microscopy is used to investigate the sequence of lithiation in LiFePO4 porous electrodes. For electrodes with homogeneous interparticle electronic connectivity via the carbon black network, the smaller particles lithiate first. For electrodes with heterogeneous connectivity, the better‐connected particles preferentially lithiate. Correlative electron and X‐ray microscopy also reveal the presence of incoherent nanodomains that lithiate as if they are separate particles.